The Effect of the United States' Granting Most Favored Nation Status to Vietnam - Martin, Will, 1953- 1953- (The World Bank, 1999)
November 1999 - If the United States grants Vietnam most favored nation status, both countries would benefit. Vietnamese exports to the United States would more than double, and Vietnam would gain substantial welfare benefits from improved market access and increased availability of imports. For the United States, lowering the current high tariffs against Vietnam would improve welfare by reducing costly diversion away from Vietnamese products. Since the U.S. embargo on trade with Vietnam was lifted in 1994, exports from Vietnam to the United States have risen dramatically. However, Vietnam remains one of the few countries to which the United States has not yet granted most favored nation (MFN) status. The general tariff rates that the United States imposes average 35 percent compared with 4.9 percent for the MFN rate. Granting MFN status to Vietnam would improve its terms of trade and help improve the efficiency of resource allocation in the country. Better access to the U.S. market would increase the volume of Vietnamese exports to the United States and the prices received for them while also reducing their costs to U.S. users. Fukase and Martin use a computable general equilibrium model to examine the effects of reducing U.S. tariffs on Vietnamese imports from general rates to MFN rates. They estimate tariff changes using the U.S. tariff schedule for 1997 weighted by Vietnam's exports to the United States. The results suggest that after a change to MFN status for Vietnam, its exports to the United States would more than double, from the 1996 baseline of